Breaking down re‐enrollment barriers for adult learners improves the college experience for all. Issue 2 (17th April 2023) - Sutton, Halley
Abstract : CHICAGO — Re‐engaging your stopped‐out adult learners can be an effective tool in your arsenal for dramatically boosting completion rates, not to mention changing the lives of the students in your community. "We know who [these students] are: when they stopped out, why they stopped out. It's rarely that they failed out, but more likely they 'lifed' out in some way, " said Tony Sheppard, Professor and Program Coordinator of Hospital Management & Tourism at Sacramento State University.